Peningkatan Motivasi Belajar Siswa Materi Menghadirkan Salat Dan Zikir Dalam Kehidupan Melalui Problem Based Learning Kelas VII SMP Negeri 4 Kecamatan Guguak - Hendri Hendri; Salmiwati Salmiwati; Rina Mala Putri (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This research is a Classroom Action Research (PTK). This study aims to determine how to increase student learning motivation in the material of presenting prayer and dhikr in the lives of students in class VII SMP Negeri 4 Guguak District. It can be seen that the results of student activity from pre-cycle to cycle I and II have improved better, especially through Problem Based Learning. This research was carried out in, the first stage is pre-cycle activities, namely looking for data on learning outcomes before using the second stage is the implementation of Cycles I and II using Through Problem Based Learning The results showed that the application of Through Problem Based Learning improved PAI learning outcomes This is evidenced by an increase in student learning outcomes from pre-cycle to cycle I, namely 74 to 82 with a percentage change in value of 10.81%. Meanwhile, the final test of cycle II was 87%. While in the final test of cycle II was 87 with a percentage change in value of 6.76%, the percentage from cycle I to cycle II was 17.56%. and learning completeness reached 100%. Based on the results of the analysis of cycle I and cycle II, it can be concluded that through Problem Based Learning can improve PAI learning outcomes on the material of Presenting Prayer and Zikir in Life Through Problem Based Learning Class VII SMP Negeri 4 Guguak District.